Do Vaccines Have a Role as a Cause of Autoimmune Neurological Syndromes? - Nicola Principi; Susanna Esposito (Frontiers Media S.A., 2020)
Vaccines are the most important preventive measure against infectious diseases presently available. Although they have led to the eradication or the elimination of some infectious diseases, concerns about safety are among the main reasons for vaccine hesitancy. In some cases, the biological plausibility of a given damage in association with the temporal association between vaccine administration and disease development makes it difficult to define causality and can justify hesitancy. Only well-conducted epidemiological studies with adequate evaluation of results can clarify whether a true association between vaccines and adverse event development truly exists. Autoimmune neurological syndromes that follow vaccine use are among these. In this narrative review, the potential association between vaccines and the development of these syndromes are discussed. Literature analysis showed that most of the associations between vaccines and nervous system autoimmune syndromes that have been reported as severe adverse events following immunization are no longer evidenced when well-conducted epidemiological studies are carried out. Although the rarity of autoimmune diseases makes it difficult to strictly exclude that, albeit exceptionally, some vaccines may induce an autoimmune neurological disease, no definitive demonstration of a potential role of vaccines in causing autoimmune neurological syndromes is presently available. Consequently, the fear of neurological autoimmune disease cannot limit the use of the most important preventive measure presently available against infectious diseases.